Unilateral Acute Angle-Closure Glaucoma After Lumbar Spine Surgery: A Case Report and Systematic Review of the Literature. Issue 5 (March 2016) - Stewart, Robert J.; Landy, David C.; Lee, Michael J.
Abstract : Study Design: A case report and literature review is presented of a patient that developed acute angle-closure glaucoma (AACG) after undergoing spine surgery in the prone position. Objectives: To report a case of AACG after undergoing spine surgery in the prone position and describe potential causes and implications for future care. Summary of Background Data: Visual loss is a devastating complication after spine surgery and is most often due to ischemic optic neuropathy. Although far less common, three cases of AACG have previously been reported, all of which were bilateral. Mydriatric agents and prone positioning were hypothesized as precipitating factors as both are known to increase intraocular pressure. In contrast to other visual loss diseases after spine surgery, AACG is amenable to treatment if recognized and treated early; however, its diagnosis is often complicated by patients presenting days after surgery. We report the case of a 65-year-old male who underwent multilevel revision spine surgery in the prone position and developed unilateral AACG after discharge on postoperative day 5. Methods: The case report is described. A literature review was performed using PubMed and keywords. The resulting articles were evaluated and references checked for additional cases. Results: The case herein resulted in no vision loss after the AACG was treated with laser iridotomy. The patient had a history of ocular issues in the affected side, highlighting the potential role anatomy plays in the development of AACG following spine surgery. Three reports of AACG were found after the literature review was performed. Conclusion: Although it is not practical to screen all patients through ophthalmologic referral, there may be a role for targeted preoperative screening of patients with risk factors for AACG. Level of Evidence: 5